Bullying no contexto escolar: prevenção e estratégias de enfrentamento - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This paper is the result of a bibliographic review carried out through scientific article readings, whith general objective of characterizing preventive actions and coping strategies to combat bullying, promoted by school community in Basic, Fundamental and Secondary Education, in Scielo’s and Google Scholar’s databases. Bullying is a set of aggressive attitudes that occur repetitively, intentionally and without motivation among peers, with power inequality causing pain and suffering to victims. Its consequences negatively affect lives of students, whether they are victims, aggressors or witnesses. The classroom is the place where bullying most occurs, and most teachers have difficulties on identifying and intervening in the problem, believing it to be a children's/adolescents' game. This way preventive actions were listed and coping strategies used at school environment in order to minimize this difficult situation.
Keywords: Bullying; Escola; Prevenção; Estratégia de enfrentamento; School; Prevention; Coping strategy; CNPQ::CIENCIAS HUMANAS